Environmental Influences Cause Stress on the Use of Computer - Wijaya, I Ketut (International Journal of Public Health Science (IJPHS), 2012)
Working with a computer over a period long enough to be done. Computer is the best medium currently in appearance and in the way of working, because the computer can assist in completing the work in a more rapid, efficient and very easy to use. With the convenience offered by the computer, almost all the work can be done with computer. Computers are a necessity in supporting work and communication tool that is quite reliable. The computer is useful in life, but can also cause problems on users, the computer can issue radiation that affects the condition of the user as well as ignorance in using computers can cause Repetitive Strain Injury (RSI). Besides, the use of computers can lead to stress as a result of incomprehension  in determining the condition of the environment on room. To be able to know the stress resulting from the use of computer, conducted research with a sample of 30 people at Udayana University Computer Science students with a design the same subject. Data analysis was performed with SPSS 13.00 and differences in the data before and after the redesigned (improvement), that do use the test independent sample t-test (t test group), at the level of significance of 5%. After a redesigned (improvement) on the environmental temperature is obtained decrease in the standard cold temperatures of Indonesia work of 28.00 C to 25.83 C, occupational stress decreased from 86% to 42%, and improve learning outcomes from 59.6% to 98.1%.. Thus It can be concluded that due to improvements made agains environmentally ergonomic standards can reduce the stress of work. Keywords: Computers; Stress.DOI: http://dx.doi.org/10.11591/ijphs.v1i1.419